Understanding Parents’ Perceptions of Children’s Physical Activity - Álvarez-Bogantes, Carlos Eduardo (2019)
Currently, there is little research on mothers’ perceptions of the social support they provide for their children to be physically active, which could yield important information in the construction of interventions that promote active lifestyles in childhood. We conducted individual interviews and three focus groups with 15 mothers of children 6 to 8 years old. The data were thematically analyzed using a qualitative approach, applying Ecological Model constructs to guide coding and categorization of results and the discussion of these results. The majority of mothers acknowledged that their sons and daughters were relatively less active and indicated that they perceived a need for increased physical activity among their children. The use of social support strategies was minimal, limited to accompanying their children. Mothers reported environmental factors such as cost, time constraints, lack of extracurricular-community activities and unsafe environments as the main barriers to their children’s physical activity. This study generated three main categories of results: the information gathered following the ecological model as a framework for analysis generated suggests that mothers are not aware of lack of physical activity of their children; mothers do not know ways to use social support for active lifestyles in their children, and recognize barriers to increase children’s physical activity. These research findings may contribute to health promotion strategies and programs that educate parents on how to effectively support their child in developing an active style of life.